1984
DOI: 10.1016/0014-5793(84)80342-7
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of suppressor seryl‐tRNA:ATP phosphotransferase from bovine liver

Abstract: Seryl‐tRNASer CmCA:ATP phosphotransferase was purified 1200‐fold from bovine liver by ultracentrifugation at 150 000 × g, chromatography on DEAE—cellulose, fractional precipitation with ammonium sulfate, chromatography on hydroxyapatite, gel filtration on Sephacryl S‐300 and affinity chromatography on Blue Sepharose. Molecular mass was estimated as 135–145 kDa. The K m values for ATP and ser‐tRNASer CmCA were 2 mM and 21 nM, respectively. This enzyme did not react with ser‐tRNASer IGA, tyr‐tRNA or thr‐tRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 17 publications
(14 reference statements)
1
22
0
Order By: Relevance
“…The serine moiety en the tRNA is 0-phosphorylated by a kinase (Mizutani and Hashimoto, 1984) and the corresponding 0-phosphoseryl-tRNA has been implicated, in a number of studies, in the insertion of 0-Pserine into protein (for a review see Hatfield ef al., 1990). Recently, evidence has been published which demonstrates that this tRNA carries selenocysteine in vivo and thus may be the homologue of the E. coli seIC gene product (Lee et al, 1989).…”
Section: Biological Distribution and Evolutionmentioning
confidence: 99%
“…The serine moiety en the tRNA is 0-phosphorylated by a kinase (Mizutani and Hashimoto, 1984) and the corresponding 0-phosphoseryl-tRNA has been implicated, in a number of studies, in the insertion of 0-Pserine into protein (for a review see Hatfield ef al., 1990). Recently, evidence has been published which demonstrates that this tRNA carries selenocysteine in vivo and thus may be the homologue of the E. coli seIC gene product (Lee et al, 1989).…”
Section: Biological Distribution and Evolutionmentioning
confidence: 99%
“…The TGA codon within this gene corresponds to a selenocysteine moiety in the gene product. We have recently shown that a minor tRNA in mammalian tissues which recognized UGA in a ribosome binding assay and was identified as an opal suppressor seryl-tRNA (6) and phosphoseryl-tRNA (10,23) is actually a selenocysteyl-tRNA (18), which is now designated as selenocysteine tRNA [Ser]Sec. These studies provide evidence that tRNA [ser]sec has a twofold function of serving as a carrier molecule upon which selenocysteine is synthesized and as a direct donor of selenocysteine to protein (e.g., glutathione peroxidase) in response to specific UGA codons (18).…”
mentioning
confidence: 99%
“…(vi) They differ in their primary sequences by several pyrimidine transitions including one in the wobble position of their anticodons (7), and these transitions must occur post-transcriptionally since both species are encoded by the same gene (9)(10)(11)(12). (vii) They are phosphorylated on their serine moiety by a kinase to form phosphoseryl-tRNA (7,13). The genes corresponding to the human (10), rabbit (11), chicken (9), and Xenopus (unpublished results) opal suppressor phosphoserine tRNAs have been isolated and sequenced.…”
mentioning
confidence: 99%
“…The fact that they read the termination codon UGA in protein synthesis (6,7) and are phosphorylated on their serine moiety (7,13) suggests that these tRNAs donate a modified amino acid directly to protein in response to specific UGA codons. A mRNA from Sindbis and from Middleburg viruses (19) and mouse glutathione peroxidase mRNAs (20) (21), which agrees with the possibility that the opal suppressor phosphoseryl-tRNA may be involved in the occurrence of selenocysteine in glutathione peroxidase.…”
mentioning
confidence: 99%